Use of the Wii Balance Board as a Mechanism for Recognition and Classification of the Risk of Falls in Older Adults; [Uso de la Wii Balance Board Como Mecanismo de Reconocimiento y Clasificación del Riesgo de Caídas en el Adulto Mayor] - De Moraes-Ferrari, G (Universidad de Murcia, 2023)
Introduction: In clinical practice, the functional tests used to assess the risk of falls require precision techniques and elements that avoid subjectivity. The use of the Wii Balance Board (WBB) is an alternative to the above, since it is an inexpensive, portable tool that allows extracting variables that are related to the phenomenon under study. Objective: To classify the variables derived from the center of pressure (CoP) during the evaluation of postural control through the WBB, in older adults with and without risk of falls. Methods: A descriptive research design was used. A total of 40 older adults were studied, 20 with and 20 without risk of falls. Postural control was evaluated using the WBB, extracting kinetic and kinematic variables, which allowed the implementation of an attribute selector and the SVM algorithm (SVMs, Support Vector Machines), identifying older adults at risk of falls. Results: The variables that best allow us to classify older adults with and without risk of falling were speed, displacement and mean force. A two-class classifier was built, whose best performance was the Kappa index 0.95 (almost perfect agreement strength), 98% sensitivity, and 100% specificity. Conclusions: The use of WBB can be considered a low-cost alternative for the evaluation of the risk of falls in older adults. © Copyright 2023.